Clinico-epidemiological study of cutaneous changes in pregnancy at a tertiary care centre in Puducherry - Ramamurthy, Janani; G. David, Brinda (International Journal of Research in Dermatology, 2023)
Background: Pregnancy causes various physiological and pathological changes of skin, due to profound immunological, endocrine and vascular changes. This study focus on these changes and hence earlier identification of pathological skin changes helps to improve both the maternal and fetal outcomes. Aims and objectives were to find the prevalence and patterns of these changes in pregnancy and also to find the association of pathological changes with gravida and gestational age. Methods: A cross sectional study was performed among 250 pregnant women with skin changes, attending dermatology outpatient department (OPD) at tertiary care centre in Puducherry and the findings were documented and the data was analyzed for statistical significance. Results: In this study, Physiological changes were most common of which linea nigra was commonly seen in (84.4%) cases (n=233) followed by striae distensae seen in (78.4%) cases (n=197). Similarly, in pathological specific dermatoses, polymorphic eruption of pregnancy was seen in (1.2%) cases (n=3), followed by atopic eruption of pregnancy was seen in (0.4%) cases (n=1). Among the pathological non-specific dermatoses, Acne vulgaris in the inflammatory diseases was seen commonly in (7.6%) cases (n=19), followed by cutaneous infections like Tinea corporis was seen in (8.4%) cases (n=21) and least common was alopecia areata seen in (0.4%) of cases among the autoimmune disorders. Conclusions: In this study physiological changes were more common in pregnant women followed by pathological non-specific and specific dermatoses. Also, there was a significant association of pathological changes with gravida and gestational age by Chi-square test with the p value <0.05.